The Semantic Map of "Aktionart" and Lexical Entailment of Old English Strong Verbs - Luisa Fidalgo Allo (Journal of English Studies, 2022)
The aim of this article is to analyse the semantic relations that hold between Old English primitive and derived verbs in terms of troponymy and Aktionsart. The results of this analysis are presented in a semantic map, while emphasis is made on the points of contact between these phenomena. The main conclusion is that semantic maps represent a more flexible and applicable methodology than previous work suggests since they have been used to deal with one language, to explain historical languages and to refer to specific lexical items. Likewise, this analysis shows evidence of an inherent relationship between both phenomena: troponymy and Aktionsart.